A Scale Development of Adaptive Performance of Hotel Staff - Supunsa Langprasert สุพรรษา หลังประเสริฐ; Kanchana Pattrawiwat กาญจนา ภัทราวิวัฒน์; กิจธรธรรม วิชุดา (Dusit Thani College Journal, 2018)
The objective of this research was to construct and develop a scale of Adaptive Performance. Data were collected by using 19 item adaptive performance scale with 280 Frontline employees, work in Hotel in Bangkok. Adaptive Performance scale was considered for its content validity by academic experts and its reliability was 0.81. The results of confirmatory factor analysis found that Adaptive Performance had 5 factors solving problems creatively, handling emergencies situations, interpersonal adaptability, training and learning effort and managing stress.The convergent validity and construct reliability of this scale were accepted. The construct reliabilities for each factor were between 0.80 and 0.91.